Sistem Keamanan Elektrik (Electrical Security System) Sebagai Antisipasi K3 pada Laboratorium Instrumentasi dan Kelistrikan Mekanisasi Pertanian Politeknik Negeri Lampung - Nurjan Didik; Puji Wiyono; Bagio Suasono (Jurusan Teknologi Pertanian, 2015)
Electrical security system is the human effort to maintain security and comfort in their environment in which he works. Not least in the laboratory instrumentation and electrical Agricultural Mechanization Polytechnic State of Lampung. As anticipate things that are not desirable in respect of negligence that often occur in the laboratory such as; AC (Air Conditioning), solder, lights and other equipment that is still alive when it is not used anymore, then used as a reference for making an electrical security system as anticipation Â Health, Safety, Work in the laboratory. The purpose of this tool is to make the security system of electricity in the laboratory of agricultural mechanization and the anticipation of Health, Safety, Work and to minimize damage to equipment as well as conserve electrical power used in addition to the manufacture of the tool also has a specific purpose; - By creating this system also can be used as a modeling tool or practicum for students primarily in Agricultural Engineering study program. - In order for students able to apply to the world of work, and apply to the community - Conducting development tools, according to the results of analysis of technical specifications as a means of research and community service for lecturers and laboratory assistant (PLP) Thus negligence or omission that could cause a short circuit in the electrical network, equipment breakdowns that led to a fire in a laboratory can be reduced or minimized, and it can save power consumption when the excessive electrical equipment is not used.Â Keywords: electrical security system, electrical power